Peran Mediasi Kinerja Lingkungan Pada Pengaruh Green Supply Chain Management Terhadap Cost Leadership - Septiano, Tyo Acyar; Widiastuty, Erna (JCA (Jurnal Cendekia Akuntansi), 2026)
This study aims to provide empirical evidence on whether environmental performance mediates the effect of GSCM on cost leadership. This study uses a quantitative approach. The study population is all public companies listed on the Indonesia Stock Exchange (IDX) in the 2020–2024 period. Sampling was conducted using purposive sampling. Based on the sampling, a sample of 61 companies was obtained with 305 company-year observations. Data analysis was conducted using the Hayes PROCESS approach. Hypothesis testing was conducted using R-Studio. The results show that GSCM has a positive and significant effect on cost leadership. However, environmental performance does not mediate the relationship between GSCM and cost leadership. The results show that GSCM practices can improve cost efficiency, but improved environmental performance requires additional costs, thus reducing the effect of GSCM on cost leadership. This study is limited to companies that have obtained a PROPER rating, so the pressure comes from regulations that better reflect compliance. Furthermore, the results of this study have limitations in generalization because they do not represent companies that do not participate in PROPER. Environmental performance variables are measured by the PROPER score, which does not reflect quantitative details such as tons of emissions, energy consumption, or waste volume. These findings provide evidence that environmental performance does not mediate the relationship between GSCM and cost leadership, implying that cost efficiency from GSCM is not automatically achieved through improved environmental performance. The underlying rationale is that environmental performance achievement is more reflective of compliance with government regulations and is not sufficient to strengthen a cost leadership position. Keywords: Cost Leadership, Environmental Performance, GSCM